The duration of playing Play Station@ as a risk factor of obesity in school age children in Yogyakarta - Ely Yulian; Endy Paryanto; Sunartini Hapsara (Indonesian Pediatric Society, 2008)
Background Childhood obesity is a common health problem.There are multi-factors causing childhood obesity. One of themis lack of activity like watching television, playing computer, andplaying Play Station@ .Objective The aim of this study was to find the duration ofplaying Play Station@ as a risk factor of obesity in school agechildren.Methods This study was a case–control study with individualmatching, that was done since April 2004 until August 2004.Results Children who spent time for playing Play Station@ morethan two hours per day had the risk of obesity 22 times higherthan those who spent less than two hours per day with 95%confidence interval. These results were analyzed with chi squaretest.Conclusion Playing Play Station@ is a risk factor of obesity inschool age children.